2020
DOI: 10.1088/1742-6596/1679/5/052001
|View full text |Cite
|
Sign up to set email alerts
|

Study of the process overcoming obstacles by tillage tools on a three-dimensional dynamometric virtual stand

Abstract: The interaction of resiliently fixed tillage tools and obstacles is investigated using computer applications that simulate the dynamics of motion of 3D models, created in CAD. The design of a virtual bench and a dynamometer block, implemented in CAD SolidWorks and an application for modeling the movement dynamics SolidWorks Motion, is described. The virtual stand allows you to simultaneously record all components of the traction resistance vector (RX, RY, RZ). With the help of a virtual stand, the volumetric f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Registered damage to cultivation tools working in stony soils or in the conditions of forest clearing requires changes in design, strength, and geometric parameters [8]. In subsequent studies [9], four types of tools were used, i.e., disc plow, cultivator disc, sweep tool, subsoiling tool, and it was found that the greatest reactions were recorded during the frontal defeat of a stump by a disc plow; and in the case of a side impact with a stump, by a subsoiler. To develop practical tools working in soils with hard obstacles, obstacle-tool interactions and the ability to overcome various obstacles must be studied.…”
Section: Introductionmentioning
confidence: 99%
“…Registered damage to cultivation tools working in stony soils or in the conditions of forest clearing requires changes in design, strength, and geometric parameters [8]. In subsequent studies [9], four types of tools were used, i.e., disc plow, cultivator disc, sweep tool, subsoiling tool, and it was found that the greatest reactions were recorded during the frontal defeat of a stump by a disc plow; and in the case of a side impact with a stump, by a subsoiler. To develop practical tools working in soils with hard obstacles, obstacle-tool interactions and the ability to overcome various obstacles must be studied.…”
Section: Introductionmentioning
confidence: 99%